Pengaruh Faktor Demografi dan Sosial Ekonomi Terhadap Status Kesehatan Individu di Sumatera Barat - Andre Sabani; Urmatul Uska Akbar; Selli Nelonda (Universitas Negeri Padang, 2023)
The study that the researchers conducted aims to make the general public know and be able to analyze the consequences of changes / emergence of the dependent variable or dependent variable. And the independent variables are education level (X1), income (X2), age (X3 gender (X4) marital status (X5) Demographics (X6) and the dependent variable is health status in West Sumatra Province (Y). Types of This research is a descriptive and inductive research.The data is secondary data taken from SUSENAS in 2022. The results of this study show that: 1) Education (X1) has a negative and insignificant relationship to individual health status.2) Income (X2) Has a negative and insignificant relationship to the health status of individual households. 3) Age (X3) has a positive and significant relationship to the health status of individual households. 4) Gender (X4) has a positive and significant relationship to the health status of individual households. 5) Marital status (X5) is not significant on individual household health status and has a negative relationship. 6) Region (X6) has a negative and significant relationship to the health status of individual households.